NEPHRON NUMBER IN THE OFFSPRING OF RATS FED A LOW PROTEIN DIET DURING PREGNANCY - Zimanyi, Monika A; Bertram, John F; Black, Jane M (Image Analysis and Stereology, 2011)
In experimental studies it has been shown that intrauterine growth retardation and reduced kidney growth during development are associated with significant decreases in nephron endowment. However, the results of previous studies may be inaccurate as nephron counts were obtained using a maceration technique, which can lead to breakdown of glomeruli, and other potentially biased techniques. In the present study, the total number of glomeruli (and thereby nephrons) in the offspring of rats fed a low (9%) or normal (20%) protein diet during pregnancy were estimated using a physical disector/fractionator technique. The offspring of rats fed a low protein diet had a significantly lower birth weight than rats fed a normal protein diet, their kidneys were smaller and they contained 30% fewer nephrons (20,386 ± 4,818 in the low protein diet vs. 28,731 ± 3,290 in the control rats). Our results, obtained using an unbiased stereological technique confirm previous findings that administration of a low protein diet during pregnancy results in reduced nephron endowment in the offspring.